Orchestration in web services and real-time communications. - Lin Lin (IEEE Communications magazine)
Web services orchestration is now being adopted for the coordination of real-time communications services, including telephony, video and multimedia communications. But do these communications services integrate into workflows in the same way as Web services in the data environment, and are orchestration mechanisms for Web services sufficient for the needs of workflows that involve real-time communications? In this article we explore these questions by taking a look at three approaches to orchestrating workflows: Business Process Execution Language (BPEL), Call Control extensible Markup Language (CCXML), and State Chart extensible Markup Language (SCXML). Through an analysis of these languages, we find that although there are similarities between BPEL as a Web services orchestration language and CCXML/SCXML as orchestration languages for telecom applications, certain key differences, namely procedural vs. event-based representation and coarse vs. fine task granularity, make it more suitable to use these two types of languages together rather than having one replace the other in converged voice-data applications.